Firm Survival through Semi-Exits: The Case of Indian Registered Manufacturing - Gupta, Priyambada (Asian Journal of Economics and Empirical Research, 2019)
The paper examines the extent to which product line change as a strategy improves the performance of firms across two manufacturing sectors over a period from 2008-2017. Durability and technology are the two dimensions chosen to identify the sectors. Hence, the paper studies electronic industry and food industry firms as the former are science-based, high-tech firms, whereas, the latter is a traditional manufacturing according to the Pavitt’s taxonomy. Additionally, food products are known to be less durable than the electronic and electrical products. The paper analyzes the data using a cross-section difference-in-differences estimation to study the difference in average performance since the strategy is not an exogenous treatment but relies on firm-specific characteristics. In Appendix 2 results from a hypothetical case is presented in which it shows how the average performance across the two sectors adopting the strategy differs had the strategy been completely exogenous. The results hint towards an overwhelming improvement in the performance for electronic industry firms showing a change in product line as compared to food industry firms not adopting the strategy. Even though it is vital in enhancing the efficiency in firms which is shown both theoretically and empirically still only a few firms adopt the strategy in the Indian market. The paper tries to find reasons for the same by using certain case studies and see how product line change may not be an ideal strategy to undertake despite its role in allocating resources efficiently.